2015
DOI: 10.1371/journal.pone.0141990
|View full text |Cite
|
Sign up to set email alerts
|

Carboranyl-Chlorin e6 as a Potent Antimicrobial Photosensitizer

Abstract: Antimicrobial photodynamic inactivation is currently being widely considered as alternative to antibiotic chemotherapy of infective diseases, attracting much attention to design of novel effective photosensitizers. Carboranyl-chlorin-e6 (the conjugate of chlorin e6 with carborane), applied here for the first time for antimicrobial photodynamic inactivation, appeared to be much stronger than chlorin e6 against Gram-positive bacteria, such as Bacillus subtilis, Staphyllococcus aureus and Mycobacterium sp. Confoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
1
8
0
Order By: Relevance
“…In this study, K + leakage was observed for all bacteria tested when PS was combined with irradiation. The results obtained corroborate the cell surface changes observed from contact angles measurements and are in agreement with another studies [ 39 ] where K + leakage was observed after aPDI. Xanthene dyes are amphiphilic molecules and according to the partition coefficients they present lipophilic tendency [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, K + leakage was observed for all bacteria tested when PS was combined with irradiation. The results obtained corroborate the cell surface changes observed from contact angles measurements and are in agreement with another studies [ 39 ] where K + leakage was observed after aPDI. Xanthene dyes are amphiphilic molecules and according to the partition coefficients they present lipophilic tendency [ 40 ].…”
Section: Discussionsupporting
confidence: 92%
“…Further studies brought positive information about the antimicrobial activity of various bis- o -dicarbaboranes, closo - o -dicarbaboranes, and nido -type dicarbollide anions towards the representatives of microscopic fungi and bacteria Staphylococcus aureus , Streptococcus pyogenes , Escherichia coli , Klebsiella pneumoniae , Mycobacterium spp., Enterobacter cloacae , Pseudomonas aeruginosa , Acinetobacter baumannii , etc. [ 36 , 37 , 38 , 39 , 40 , 41 ]. More information about these properties was published in an article focused on the antimicrobial activity of COSAN derivatives [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial photodynamic therapy or inactivation (aPDT or aPDI) is new effective method of killing gram-negative and gram-positive bacteria and yeast [33][34][35][36]. aPDI employs a non-thermal reaction induced by the interactions between visible light photons and a photosensitizer, such as methylene blue, chlorin, porphyrin, chlorophyll or their derivatives, in the presence of oxygen.…”
Section: Photosensitizersmentioning
confidence: 99%